A probiotic product elaborated using Lupinus mutabilis sweet (chocho or tarwi) seeds - Castañeda Castañeda, Benjamín (2018)
Introduction: Tarwi is an ancient leguminous plant that has been grown for many centuries in the Andean region. It has rich protein and fat contents, and since it has probiotic actions it may be used as a nutritional supplement in dairy products in Peru.Objective: To establish preliminary tests for the formulation and elaboration of a yogurt product using tarwi flour, aiming at the acceptability of such a product.Material and method: An experimental development study performed with Lupinus mutabilis Sweet for the development of a nutritional yogurt formulation incorporating Tarwi flour, and with nutritional, sensorial, and microbiological assessment.Results: Two mixtures incorporating different concentrations were elaborated (YSPT1; 70% powder milk + 30% tarwi flour), (YSPT2; 80% powder milk + 20% tarwi flour). Total solid contents in the mixtures were between 12 to 14%. Protein contents were 3,86% and 3,93%; fat contents were 2,88% and 3,0%; carbohydrate contents were 14,04% and 14,13%; and energy contents were 97,57 and 99,33 kcal, respectively. Acidity tests were performed, looking for percentages of lactic acid. Samples were assessed for 8 hours in an environment between 42 to 44ºC temperature. Results indicated that YSPT1 and YSPT2 had 0,39% and 0,41% acidity, respectively. Sensorial characteristics, such as odor, taste and acceptability did not show any statistically significant difference according to an analysis of variance (ANOVA), with a p<0,005 significance level. However, general average values reported that evaluators preferred YSPT2 compound (80% powder milk + 20% tarwi flour). According to the hedonic scale used, they experienced a moderately pleasant sensation when ingesting the product. Microbiological results for the presence of coliform bacteria, fungi and moulds showed <10 cfu/g per sample in both concentrations.Conclusions: These results offer a good likelihood for using this leguminous plant for the elaboration of products that are similar on the market.